Land and Law in Marijuana Country: Clean Capital, Dirty Money, and the Drug War's Rentier Nexus. Issue 2 (28th October 2013) - Polson, Michael
Abstract : Despite its ongoing federal illegality, marijuana production has become a licit, or socially accepted, feature of northern California's real estate market. As such, marijuana is a key component of land values and the laundering of "illegal" wealth into legitimate circulation. By following land transaction practices, relations, and instruments, this article shows how formally equal property transactions become substantively unequal in light of the "il/legal" dynamics of marijuana land use. As marijuana becomes licit, prohibitionist policies have enabled the capture of ground rent by landed interests from the marijuana industry at a time when the price of marijuana is declining (in part due to its increasing licitness). The resulting "drug war rentier nexus, " a state–land–finance complex, is becoming a key, if obscured, component within marijuana's contemporary political economy.